Studying the effect of silymarin against oxidative stress induced by chemotherapeutic protocol in breast cancer women - Bahir Abdul Razzaq; Mohammad R.I. Ghazal; Khalid A. Al-Khazragy; Khudder Jasim Al-Rawaq (College of Pharmacy / Mustansiriyah University, 2011)
Breast cancer became the commonest type of cancers among Iraqi women since the last two decades. The main underlying cause is thought to be DNA damage; much of which is oxidative in nature. CAF protocol (Cyclophosphamide + Adriamycin + 5-FU) associated with toxic effects in several body organs, mainly through production of free radicals and reactive oxygen species. Silymarin, the dried extract of a ripe seeds of the plant silybium marianum, was found to be a powerful antioxidant protective agent against toxin -induced tissue damage .The objective of this study is to evaluate the possible time and dose-dependent protective effect of the orally administered silymarin as antioxidant agent against oxidative stress induced by CAF protocol (mainly Adriamycin) in breast cancer women. This study included 94 subjects, 20 were healthy control women (for matching with oxidative stress markers) and 74 were breast cancer women that randomly distributed and allocated into three groups: Group (A): Include 24 patients who received CAF protocol by I.V infusion once every 21 days and for 63days. Group (B): Include 25 patients who received 210mg/day of along with the same CAF protocol of group (A); Group (C): Include 25 patients who received 420mg/day of silymarin along with the same CAF protocol of group (A). Oxidative stress markers (MDA and GSH) were measured at baseline (zero time), after 21, 42, and 63 days of treatment for each patient group. Our results showed an increase in the oxidative stress for both baseline patients and those treated with CAF protocol, manifested by significant increase in MDA levels and GSH depletion, a state which is significantly reversed by use of silymarin, in a time and dose-dependent manner. Breast cancer and its antineoplastic CAF protocol produce free radicals which attenuate antioxidant defense mechanism of the body leading to several toxic effects on different body organs, so the use of antioxidant agent (silymarin) in this study may ameliorate, in a time and dose-dependant manner,theharmfuleffects of this protocol.